Phonetics and phonology as an intervention strategy to improve english learning among brazilian students - ROCHA, Danilo Oliveira (2023)
This study aims to discuss students’ perceptions concerning listening and speaking, suggesting phonetics and phonology as an intervention strategy to help them in their learning process. As a tool to collect the necessary data for this study, a questionnaire was designed and applied at a private school of languages in Altamira/PA and it took four weeks. The subjects involved in the research are eight students, (beginners, intermediate and advanced). As theoretical background, we searched for Brown (1994), Harmer (1998), Krashen (1982), Roach (2009) and Wilson (2008). As a result, students’ reports demonstrated that there are many difficulties and worrying about the skills mentioned, otherwise they have some techniques to deal with these challenges, and small actions already developed by the teachers in class have helped them a lot in their learning process, making us realize the importance of dedicating attention and fortifying activities focused in phonetics and phonology, having learners more aware about English features when it comes to speaking and listening skills.